2014
DOI: 10.1261/rna.046060.114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microRNA differential expression and detection in multiplexed small RNA sequencing data

Abstract: Small RNA sequencing can be used to gain an unprecedented amount of detail into the microRNA transcriptome. The relatively high cost and low throughput of sequencing bases technologies can potentially be offset by the use of multiplexing. However, multiplexing involves a trade-off between increased number of sequenced samples and reduced number of reads per sample (i.e., lower depth of coverage). To assess the effect of different sequencing depths owing to multiplexing on microRNA differential expression and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The variations observed between two time points in number of reads mapped to miRNAs may have contributed to the inter-experiment variations in the total and miRNAmapped reads, but it did not influence the time-matched comparisons between pIC and control groups at 24 HPS and 72 HPS. However, the lower number of reads mapped to miRNAs in the pIC-treated samples compared to time-matched controls at 72 HPS may have affected the sensitivity of detection of differentially expressed miRNAs at this time point (Campbell et al, 2015). Some significant pIC-responsive miRNAs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The variations observed between two time points in number of reads mapped to miRNAs may have contributed to the inter-experiment variations in the total and miRNAmapped reads, but it did not influence the time-matched comparisons between pIC and control groups at 24 HPS and 72 HPS. However, the lower number of reads mapped to miRNAs in the pIC-treated samples compared to time-matched controls at 72 HPS may have affected the sensitivity of detection of differentially expressed miRNAs at this time point (Campbell et al, 2015). Some significant pIC-responsive miRNAs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of miRNAs/genes expression in microarray data sets was consistently different due to different platforms and different batches [ 46 ][ 15 ]. All statistical data sets were normalized and standardized to be approximately equal in scale and normally distributed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the total number of mapped reads from the three donors across both kits was comparable ( Figure S3B, paired t-test between Truseq and Nextflex for mapped read was not significant with a p-value of 0.15), as was the type of RNA detected by each kit (Fig S3C). Since small RNA sequencing kits are commonly used to study miRNA expression [16], we compared the unique miRNAs mapped by each kit. We found that the Nextflex kit identified about 150 more unique miRNAs compared to the Truseq kit across donors (Figure 4(b), p-value = 0.01).…”
Section: Choice Of Library Preparation Impacts the Mirna Sequences Dementioning
confidence: 99%